Distance learning and its role in achieving satisfaction with learning goals and outcomes in light of the Corona Pandemic from the point of view of basic education teachers in public schools in Zarqa city - Al-Malaheem, Mariam Atieh (Journal of Educational and Psychological Sciences, 2022)
The current study aimed to know the role of distance learning in achieving satisfaction with the goals and outcomes of learning in light of the Corona pandemic from the point of view of the teachers of the basic education stage. randomly. Using the proportional random method with each sub-category in the study community, the researcher relied on the questionnaire as a tool for data collection. The questionnaire consisted of four main axes distributed over 43 items. After statistical analysis, the study provided a set of foundations and skills that help female teachers to master distance learning skills. In light of the Corona pandemic, the results indicated the importance of the role of distance learning in achieving satisfaction with the learning objectives and outcomes for female teachers of the basic education stage in light of the Corona pandemic, where the general average of the opinions of the study sample was (4.27).With a response that strongly agrees, it also indicated that the basic education stage teachers were not satisfied with the goals and outcomes of learning using distance learning, as an educational style in light of the Corona pandemic in its current situation, where the general average of the opinions of the female teachers (2.09) came with a rare response, and the views of the teachers about the factors that helps to achieve satisfaction with the objectives and outputs The learning of the female teachers of the basic education stage when using distance learning in light of the Corona pandemic, with a general average of (4.27) with a very agreeable response.The study also recommended intensifying training courses for teachers regarding providing them with strategies for dealing with the Internet and employing it in the teaching-learning process, and motivating teachers financially and morally to encourage them to attend training courses, and choosing the appropriate time to hold courses in proportion to the teachers’ spare time.
Keywords: Distance learning; learning outcomes; Corona pandemic; the basic education stage